Impact of Migration among Farmers of Surkhet, Nepal - Magar, Esther Budha; Sharma, Bhawani; Budha, Bhumi Kumari; Khatri, Ghana Shyam; Gurung, DB; Marhatta, Deepak (Journal of Multidisciplinary Research Advancements, 2024)
Despite 66% of people’s engagement in agriculture in 2021, shifts from farming to adopting alternative jobs have been observed due to reduced income and poverty, leading to migration. Arable lands are left abandoned due to a shortage of farmers across Nepal. The research objectives were to assess the status of assets among farmers with any family members who migrated and those who did not migrate and to understand farmers’ opinions regarding external migration. A cross-sectional study was conducted randomly through a lottery in wards 2 and 11 of Birendranagar municipality in Surkhet district. The study purposively selected seventy-five farmers and prepared semi-structured questionnaires, which we pretested among 10% of farmers. After obtaining written informed consent, the data were entered in Excel and analyzed in SPSS version 16. Out of 64 farmers holding agricultural land, the majority without migrated family members (54.7%) had their land, whereas 3.1% of farmers left their rain-fed agricultural land barren. 24.2% of farmers without any migrated members reared 11 to 20 livestock, compared to 12% of farmers with migrated members in the family. 53% of farmers without migrated members planted trees within their lands, compared to 34.7% having migrated members. 84% of farmers believe external migration is essential, whereas 16% believe in staying in their homeland and continuing agriculture. The farmers without any migrated family members were observed to have more agricultural land, rear livestock, and plant trees around their houses. The majority of farmers were found to believe that external migration is vital for development, and they expressed their interest in shifting towards alternative jobs if provided with the opportunities. In the long term, the interests of farmers may lead to a shortage of agricultural labor and food insecurity.